Clinical Significance of Cerebrospinal Fluid Dynamics In Chronic Ischemic Processes of the Brain - Nargiza Shukhratovna Muzafarova; Farrukh Shukhratovich Chuliev (American Journal of Biomedicine and Pharmacy, 2025)
Disorders of cerebrospinal fluid (CSF) dynamics play a critical role in the development of chronic cerebral ischemia, particularly in cases of dyscirculatory encephalopathy (DE). Chronic ischemia arises from impaired cerebral blood flow, which results in prolonged oxygen and nutrient deprivation within neural tissues. This deficit fosters progressive degenerative changes in the nervous system. Altered CSF circulation further exacerbates ischemic and hypoxic injury to brain structures. Numerous studies have shown that impaired CSF outflow combined with elevated intracranial pressure can intensify vascular dysfunction, leading to persistent cognitive impairments, emotional instability, and various neurological symptoms. Employing a comprehensive management strategy including the assessment and correction of CSF dynamic disturbances is therefore crucial for patients with chronic cerebral ischemia, as it contributes to improved clinical outcomes, enhanced quality of life, and a slower progression of the pathological process.